2011
DOI: 10.1111/j.1365-2702.2010.03466.x
|View full text |Cite
|
Sign up to set email alerts
|

Minimising preoperative anxiety with music for day surgery patients – a randomised clinical trial

Abstract: Finding multimodal approaches to ease discomfort and anxiety from unfamiliar unit surroundings and perceived risks of morbidity (e.g. disfigurement and long-term sequelae) is necessary to reduce preoperative anxiety and subsequent physiological complications. This is especially true in the day surgery setting, where surgical admission times are often subject to change and patients may have to accommodate on short notice or too long a wait that may provoke anxiety. Our results provide additional evidence that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 24 publications
1
31
1
5
Order By: Relevance
“…Music is a well‐studied intervention to reduce anxiety for patients who undergo a variety of medical procedures. In a prospective randomized controlled trial by Ni et al, it was found that patients who listened to music prior to undergoing elective procedures reported decreased anxiety, heart rate, and blood pressure compared with patients who did not listen to music . Our study found no significant differences in anxiety even when patients listened to music during the procedure.…”
Section: Discussioncontrasting
confidence: 47%
“…Music is a well‐studied intervention to reduce anxiety for patients who undergo a variety of medical procedures. In a prospective randomized controlled trial by Ni et al, it was found that patients who listened to music prior to undergoing elective procedures reported decreased anxiety, heart rate, and blood pressure compared with patients who did not listen to music . Our study found no significant differences in anxiety even when patients listened to music during the procedure.…”
Section: Discussioncontrasting
confidence: 47%
“…; Ni et al . ). However, their effectiveness during the perioperative experience, and the clinical setting in general, is not well established and needs further reinforcement and robust evidence before they can be included as part of the healthcare service (Bratton et al .…”
Section: Introductionmentioning
confidence: 97%
“…As one of the nonpharmacologic methods for relieving patient anxiety and pain, music has historically been used in medicine, including the perioperative period, in hospice care, and during labor, cancer treatment, and lumbar puncture [33][34][35][36][37][38][39][40][41][42][43]. More recent studies have examined the effect of music during various endoscopic procedures, but a unified conclusion has not been reached to date.…”
Section: Introductionmentioning
confidence: 99%